1994
DOI: 10.1073/pnas.91.23.10829
|View full text |Cite
|
Sign up to set email alerts
|

Induced gene expression of the hypusine-containing protein eukaryotic initiation factor 5A in activated human T lymphocytes.

Abstract: The hypusine-containing protein eukaryotic initiation factor 5A (eIF-5A) is a cellular cofactor critically required for the function of the Rev transactivator protein of human immunodeficiency virus type 1 (HIV-1). eIF-5A localizes in the nuclear and cytoplasmic compartments of mammalian cells, suggesting possible activities on the level of regulated mRNA transport and/or protein translation. In this report we show that eIF-5A gene expression is constitutively low but inducible with T-lymphocyte-specific stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…In yeast expression, eIF5A has been reported to correlate with cell proliferation (7). Further, eIF5A expression was induced in activated human T lymphocytes (10). This paradox could be reconciled by viewing the mechanisms of eIF5A not as isolated circuits, but as part of a coordinated process, which targets key nodes of cell signal networks for cell growth or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast expression, eIF5A has been reported to correlate with cell proliferation (7). Further, eIF5A expression was induced in activated human T lymphocytes (10). This paradox could be reconciled by viewing the mechanisms of eIF5A not as isolated circuits, but as part of a coordinated process, which targets key nodes of cell signal networks for cell growth or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the factor interacts with the general nuclear export receptor CRM1 during their transportation from the nucleus to the cytoplasm (9). The eIF5A protein expression was normally very low but inducible with T lymphocyte-specific stimuli in human peripheral blood mononuclear cells of healthy individuals, and a significant up-regulation of eIF5A mRNA was found in the peripheral blood mononuclear cells of human immunodeficiency virus type 1-infected patients (10). The eIF5A expression is also significantly increased during dendritic cell maturation, and hypusine formation appears to be essential for this process (11).…”
mentioning
confidence: 88%
“…It has been reported that, in mammalian cells, eIF-5A is present both in the cytoplasm and nucleus [3]. The reason that eIF-5A is named as an initiation factor comes from earlier observations that it can be isolated from the ribosome-bound fraction and is considered to be involved in the first step peptide bond formation in translation [4].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the example mentioned above, an appropriate relation between the increase of eIF5A mRNA level and its protein in stimulated lymphocytes was found (4) . However, this relation is not found in some transcripts, because the mRNAs can be differentially recruited to translation process.…”
Section: Transcriptome Analysis Limitationsmentioning
confidence: 99%
“…For instance, unstimulated T lymphocytes present a low rate of eIF5A gene transcriptional activity. However, stimulation by specific mediators leads to an increase in the rate of eIF5A transcription (4) . In this context, the differential transcriptome analysis in relation to coding mRNAs of protein isoforms has to be carefully interpreted, because some systems are not able to make a distinction due to their high identity.…”
Section: Eif5a and The Mrnas Metabolismmentioning
confidence: 99%